2016
DOI: 10.1002/bip.22862
|View full text |Cite
|
Sign up to set email alerts
|

Review: Mechanochemistry of the kinesin‐1 ATPase

Abstract: Kinesins are P‐loop NTPases that can do mechanical work. Like small G‐proteins, to which they are related, kinesins execute a program of active site conformational changes that cleaves the terminal phosphate from an NTP substrate. But unlike small G‐proteins, kinesins can amplify and harness these conformational changes in order to exert force. In this short review I summarize current ideas about how the kinesin active site works and outline how the active site chemistry is coupled to the larger‐scale structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 41 publications
4
72
2
Order By: Relevance
“…It is built up based mainly on three pieces of experimental and computational evidence and/or arguments. (a) The experimental data showed that the kinesin head in the nucleotide-free, ATP, or ADP.P i state has a strong interaction with MT, whereas in the ADP state, it has a weak interaction [39][40][41][42][43][44]. The structural data showed that the strong interaction of MT tubulin heterodimer with the kinesin head in the strong MT-binding state induces large conformational changes in the tubulin heterodimer [45].…”
Section: The Modelmentioning
confidence: 99%
“…It is built up based mainly on three pieces of experimental and computational evidence and/or arguments. (a) The experimental data showed that the kinesin head in the nucleotide-free, ATP, or ADP.P i state has a strong interaction with MT, whereas in the ADP state, it has a weak interaction [39][40][41][42][43][44]. The structural data showed that the strong interaction of MT tubulin heterodimer with the kinesin head in the strong MT-binding state induces large conformational changes in the tubulin heterodimer [45].…”
Section: The Modelmentioning
confidence: 99%
“…Conventional kinesin (kinesin‐1) is a motor protein having two identical N‐terminal heads connected together by a coiled‐coil stalk through their neck linkers (NLs) . The motor can move processively on microtubule (MT) protofilaments toward the plus end by hydrolyzing ATP.…”
Section: Introductionmentioning
confidence: 99%
“…The ATP hydrolysis cycle is coupled to conformational changes within the motor and neck domains that result in forward movement of the tail attached cargo. ATP turnover drives a sequence of conformational changes that cyclically change the microtubule binding affinity of the motor domains [1]. Kinesin motors exist in all eukaryotes and have been divided into 15 families based on the position and sequence homology of their motor domain [2,3].…”
mentioning
confidence: 99%